ChemInform Abstract: Control of Oligomerization and Oxidation Steps in the Synthesis of Tris(pentafluorophenyl)corrole. Issue 36 (September 2015) - Blumenfeld, Carl; Fisher, Katherine J.; Henling, Lawrence M.; Grubbs, Robert H.; Gray, Harry B.; Virgil, Scott C.
Abstract An improved and scalable synthesis of the title compound (III) is presented.